Synthesis, characterisation, and effects of molecular structure on phase behaviour of 4-chloro-1, 3-diazobenzene bent-core liquid crystals with high photosensitivity. Issue 4 (16th March 2022) - Lu, Jinying; Qu, Yi; Yan, Daoren; Zhang, Zhiyong; Guan, Jintao; Zhang, Zelong
ABSTRACT: A series of new compounds were synthesised by adding azo functional groups and chlorine substituent to the central bent-cores to form a 4-chloro-1, 3-dizaophenylene bent-core. The structure, mesogenic properties, and photosensitivity of these compounds were characterised. The results show these synthesised compounds exhibit a broad temperature window up to 63.8°C for nematic phase and the rapid rate of trans – cis photoisomerisation. For instance, at 95°C, compound 4c in nematic phase became an isotropic liquid under UV-irradiation in 3 s and could be restored to nematic under natural visible light in 5 s. Quantum mechanics calculation confirms that using azos instead of esters as the central linkages can effectively reduce the molecular dipole moment, which appears to promote favourable mesogenic and photonic characteristics. Moreover, varying the carbon number in the terminal alkyl chains can alter molecular dipole moment and polarisability anisotropy, which are strongly correlated with the phase transition temperature and temperature range of the nematic phase. These findings suggest that 1) changing azo group position can effectively alter the intermolecular interactions by varying molecular polarity and polarisability; 2) reducing long-range electrostatic interactions can promote favourable mesogenic and possibly photonic properties of azobenzene bent-core liquid crystal. Graphical abstract: uf0001